Pure space : expanding the public sphere through public space transformations in Latin American spontaneous settlements - Silva, Elisa (Architecture professor) (Actar Publishers, 2020)
This book may seem a simple accumulation of twenty-one public space projects in eight Latin American cities. On closer inspection, the presentation of project descriptions, photographs, and annotated drawings reflects a concern to analytically explain the operative aspects at work. The publication is not intended to serve only as a catalogue, guide, or manual on how to produce public space in spontaneous settlements. Rather, it goes beyond the aims of an index of best practices. It is intended, instead, as an empirical base for a critical and theoretical engagement with the problematic of development, social inclusion, public investment, (in)formal settlement, civil society and the public sphere. The publication achieves its final function at this third level, by providing a compelling argument to expand the agency of architects and urban designers and creatively find ways of justifying, financing, and building public spaces in communities - spaces that have a catalytic effectiveness in achieving significant urban and social transformation.